COLLABORATIVE GOVERNANCE DALAM PENETAPAN BATAS DESA PELAJARAN KABUPATEN LAHAT - Armansaputra, Deni; Febriyanti, Doris; Amaliatulwalidain, Amaliatulwalidain (CV The Journal Publishing, 2024)
This study explores the implementation of Collaborative Governance to accelerate the establishment of village boundaries in Pelajaran Village, Jarai District, Lahat Regency, South Sumatra. This approach involves synergy between local government, village communities, and other relevant parties. Active participation of the village community, who have local knowledge and direct interests, is crucial in this process, ensuring that decisions reflect their needs and aspirations, and garnering strong legitimacy and support. Coordination among government institutions, including city, district, and regional governments, is a key element in the success of this governance, helping to overcome bureaucratic challenges and technical constraints to expedite decision-making. Transparency and accountability at every stage of the village boundary establishment process enhance public trust and prevent fraud and abuse of power. Peaceful conflict resolution through dialogue and negotiation is a key advantage of this governance, addressing potential conflicts among residents or between villages with fair and acceptable solutions for all parties. The research findings indicate that good collaboration among stakeholders can lead to effective, fair, and widely accepted decisions.